Analisis Kepercayaan Dan Risiko Menggunakan Metode Technology Acceptance Model Dalam Penggunaan Mobile Banking Pada Pt. Bank Sumsel Babel Cabang Kayuagung - Cynthia Anisa Agatha; Edi Surya Negara Harahap (Jurnal Ilmiah Informatika, 2024)
Banking is an institution that carries out activities in the form of activities to collect funds from the public and channel them in the form of loans or financing. In general, customers tend to use mobile banking based on various factors, including convenience, comfort and trust in the technology. One method that can be used to measure interest in using information technology is to use the Technology Acceptance Model (TAM). Based on observations made on several respondents who have used the South Sumatra Babel Bank mobile banking application, it can be said that interest in using the application does not make users bored or lazy about using it. The guarantee is that users will be given ease in using the mobile banking application.